2002
DOI: 10.1021/jf020358+
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Arabinoxylans from Bajra (Pearl Millet)

Abstract: Structures of arabinoxylans (AX) from bajra, from a variety known to have characteristic quality in the making of roti, an unleavened flat bread, were elucidated by a combination of methylation analysis, (13)C NMR, FT-IR, etc. Arabinoxylans isolated from barium hydroxide-extracted polysaccharides and hemicellulose B had a backbone of xylose residues with beta-(1,4) linkages and were branched mainly through alpha-(1,3) linkages by arabinofuranosyl residues. Completely branched xylose residues were also present.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In accordance with Nandini and Salimath (2002), distinct C-1 signals (110.0 and 109.8) were ascribed to T-a-L-Araf. These terminal residues must be differentially linked to the backbone of the arabinan chain, as will be discussed bellow.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In accordance with Nandini and Salimath (2002), distinct C-1 signals (110.0 and 109.8) were ascribed to T-a-L-Araf. These terminal residues must be differentially linked to the backbone of the arabinan chain, as will be discussed bellow.…”
Section: Resultssupporting
confidence: 60%
“…1 shows the 13 C NMR spectrum of the purified arabinan-rich pectic polysaccharide. Based on spectral data from arabinans (Capek, Toman, Kardosova, & Rosik, 1983;Cardoso et al, 2002;Habibi, Mahrouz, & Vignon, 2005;Joseleau, Chambat, & Lanvers, 1983;Swamy & Salimath, 1991;Vignon, Heux, Malainine, & Mahrouz, 2004), arabinoxylans (Broberg, Thomsen, & Duus, 2000;Nandini & Salimath, 2002;Roubroeks, Andersson, & Å man, 2000), and pectins (Habibi, Heyraud, Mahrouz, & Vignon, 2004;Pressey & Himmelbach, 1984;Ryden, Colquhoun, & Selvendran, 1989), 13 C 1 signals were assigned to the following a-L-arabinofuranosyl Fig. 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some studies have shown that arabinoxylans could increase flour quality due to increased flour water absorption, dough formation time and stability time (Ingelbrecht et al, 2000;Frederix et al, 2004;Guttieri et al, 2008). The quality of bread products may be improved by increased crumb structure and extended bread shelf life (Nandini & Salimath, 2002;Cyran et al, 2003;Muralikrishna & Rao, 2007). However, other studies showed that arabinoxylans had little effect on the volume of baked products or even caused decreased bread volume (Jelaca & Hlynca, 1972;Kim & D 'Appolonia, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Both O‐2‐ and O‐3 branched xyloses were few in number. Structures of AX from wheat can be compared with those studied by us from other cereals such as sorghum46 and bajra47 which are known for their roti ‐making quality. The AX from sorghum and bajra were more branched than wheat AX.…”
Section: Discussionmentioning
confidence: 95%